Factors affecting mothers' choice of breastfeeding vs. formula feeding in the lower Umfolozi district war memorial hospital, KwaZulu-Natal - Susan Swarts; H. Salome Kruger; Robin C. Dolman (AOSIS, 2010)
The aim of this study was to determine which factors influence choice of breast- versus the formulafeeding of infants. This may help to understand where the focus should lie in the promotion of breastfeeding. A structured questionnaire was completed by a 100 women and focus-group discussions were held with 22 women who delivered babies at the Lower Umfolozi District War Memorial Hospital (LUDWM) in Kwazulu-Natal. Most of the mothers (72%) chose breastfeeding and 58% intended to breastfeed for only 6 months. One-third (33%) were influenced by health care professionals and 44% of the mothers made their own decisions in their feeding method. Only one participant stated that she chose formula-feeding due to her HIV-positive status, but in the focusgroup discussions, the fear of transmission of HIV through breast-milk was stated as an important reason why mothers chose replacement-feeding. Significantly more HIV-infected than uninfected mothers chose replacement-feeding as the feeding method and mothers who chose breastfeeding were significantly older than mothers who selected replacement-feeding. They made their infantfeeding decision earlier than those who chose replacement-feeding. Findings showed that the majority of women in this study did not have access to running water and flush toilets in their houses.In these areas where replacement-feeding will not be acceptable, feasible, affordable, sustainable and safe, due to lack of sanitation and poor socio-economic status, health professionals should promote exclusive breastfeeding for 6 months, even though there is a high prevalence of HIV infection. Opsomming Die doel van die studie was om te bepaal watter faktore vroue in hulle keuse van bors- of bottelvoeding beïnvloed. Dit sal help om te verstaan op watter faktore gesondheidswerkers moet fokus wanneer borsvoeding bevorder word. 'n Gestruktureerde vraelys is voltooi deur 100 vroue en fokusgroepbesprekings is met 22 vroue wat by die Laer-Umfolozi Distrik Gedenk-hospitaal(LUDWM) geboorte geskenk het gehou. Die meerderheid vroue (72%) het borsvoeding gekies,58% het voorgeneem om vir 6 maande te borsvoed. 'n Groot aantal vroue (97%) het inligting oor babavoedingskeuses by gesondheidswerkers ontvang. Een derde van die vroue (33%) is deur die gesondheiswerkers beïnvloed en 44% van die deelnemers het aangedui dat niemand hulle beïnvloed het nie. Beduidend meer MIV-geïnfekteerde as ongeïnfekteerde moeders het kunsvoeding bo borsvoeding verkies. Net een moeder het gerapporteer dat sy kunsvoeding gekies het as gevolg van haar MIV-positiewe status, maar in die fokusgroepbespreking is die mening gelug dat die vrees van MIV oordrag deur borsmelk grootliks bygedra het dat MIV geïnfekteerde moeders kunsvoeding gekies het. Die moeders wat borsvoeding gekies het was beduidend ouer en het die voedingsmetode beduidend vroeër gekies as die wat kunsvoeding gekies het. Die resultate dui aan dat kunsvoeding nie aanvaarbaar, uitvoerbaar, bekostigbaar, volhoubaar en veilig is in die studie-area nie, as gevolg van swak sanitasie en die swak sosio-ekonomiese toestande. Gesondheidswerkers behoort dus eksklusiewe borsvoeding vir die eerste ses maande te bevorder, al is die prevalensie van MIVinfeksie.